Approaches to History Teaching According to a Structural Equation Model - Guerrero-Romera, Catalina; Sánchez-Ibáñez, Raquel; Miralles-Martínez, Pedro (Frontiers in Education, 2022)
Approaches to the teaching and learning of history imply a series of changes and improvements which are adapted to the new epistemological and disciplinary contexts. This calls for a series of transformations in teaching approaches and methodological strategies in order to bring them more into line with the current model of history education. The purpose of this article is to analyse the validity of a questionnaire designed to identify the perceptions of in-service teachers regarding the teaching approaches they believe to be most appropriate for teaching history in primary and secondary/baccalaureate education in Spain. The research methodology employed was quantitative with a non-experimental design based on a Likert-type questionnaire. The sample is non-probabilistic and consists of 332 active teachers who teach history in primary and secondary/baccalaureate education in Spain. For the analysis of the data, a structural equation model was used based on exploratory and confirmatory factor analyses. The results indicate that the teachers surveyed identify three teaching approaches in accordance with the theoretical approach underlying the research. Specifically, a traditional approach based on the memorisation of content; an intermediate model in which there is interaction between teachers and students, through strategies such as discussion, and a third focused on students and the development of historical and critical thinking. These results have important implications for the initial and on-going training of teachers, especially in terms of content.